TINJAUAN HUKUM ISLAM DAN HUKUM POSITIF TERHADAP PRAKTIK JASA KONVERSI PULSA MENJADI UANG - Aisyah; Irvan Iswandi (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2022)
The practice of exchanging pulses for money (known as converting pulses) is widespread. The absence of rules regarding distribution and use makes pulses a medium of exchange for cyber crimes. The objectives to be achieved in this study are to describe how the mechanism of the practice of converting telecommunications pulses into money and to explain how Islamic law and positive law review the practice of converting telecommunications pulses into money. This type of research uses field research (FieldResearch), which is a research which is done by lifting data in the field with actual events. The population in this study are providers and users of credit conversion services. Data collection techniques with interviews, and documentation. Methods of data processing by editing, organizing, and analyzing. Based on the results of research regarding the use of services to convert pulses into money. the author can draw the following conclusions: The conversion of credit into money is permissible according to Islamic law as long as it does not conflict with sharia. The contract used in this practice can be equated with an ijarah contract. As for the conversion rate, which results in a difference in the amount of credit and the converted money, it becomes permissible and not usury. However, if the practice is carried out with clear and obvious intentions that it is prohibited by the Shari'a and the origin of the credit to be converted comes from things that are prohibited by Islam, then the law is unlawful and the practice is not allowed. In addition, until now the government has only regulated the use of credit to access applications such as set forth in the Regulation of the Minister of Communication and Informatics Number 9 of 2017 concerning the provision of content on cellular mobile networks. Both operators and regulators